River Space Use Patterns: Case of the Barito River Bank, Banjarmasin – Indonesia - Parida Angriani; Eva Alviawati (JPG (Jurnal Pendidikan Geografi), 2026)
The Barito River is a vital waterway whose banks are extensively occupied by local communities. Without proper management, these areas risk becoming slums, with serious socio-economic and environmental consequences. This study analyzes the spatial utilization patterns of riverbank settlements in the South Alalak, North Kuin, and Kuin Cerucuk Subdistricts of Banjarmasin. Data were obtained through field surveys and questionnaires from 307 purposively selected households residing within 100 meters of unembanked riverbanks. The data were analyzed both descriptively and quantitatively, and discussed in relation to government policies on river management. Findings reveal two key dimensions. Non-physical aspects reveal that most households have low incomes, work in the informal sector, and have limited education, with long-term and inherited residency being common, despite secure land ownership. Physical aspects indicate that mixed residential–commercial stilt houses predominate, supported by minimal infrastructure, including inadequate wastewater and solid waste management, narrow alleyways for circulation, insufficient public facilities, and a lack of green space. The analysis highlights that socio-economic vulnerability directly shapes spatial configurations, reinforcing environmental degradation and limiting community resilience. Based on the findings, the study recommends an integrated spatial–environmental management strategy that links household conditions with urban policy, emphasizing improved infrastructure, waste management, and provision of social–public spaces to support sustainable riverbank development.